I am Saartjie Baartman: re-imagining parts of a life - Levin, Nobunye N. (My University, 2010)
ABSTRACT Public articulations of Saartjie Baartman have focused on an over-determinism of her figure, as a signifier of European cultural and scientific imperialism. This generated a range of articulations, which utilise Baartman as a focal point in discussions of race, gender, sexuality and nation. This symbolic utilisation elides a sense of Baartman‟s private life and does not consider her self-determinism. This report and the accompanying film project, I am Saartjie Baartman, offer a re-imagining of Saartjie Baartman and her experiences. This re-imagining privileges a gendered reading of her private life through utilising a “ruin of representation”. This ruin of representation is about an “ontology of change” that seeks to “ruin” static structures of life, space and time. It is therefore located in a “logic of difference”. The “logic of difference”, for the purposes of this research, is about an interpretation of Baartman‟s subjectivity. Furthermore, this re-imagining of Baartman situates itself within the “empirical avant garde”. The “empirical avant garde sketches a geography of relations” and considers and produces a sense of experiential rather than historic (linear) time. This is imperative for Baartman‟s re-imagining as it privileges the personal and experiential. This “ruin of representation” and the re-imaging that it enables can however only exist in the film I am Saartjie Baartman. Beyond the film it reproduces itself therefore disavowing the impression of “ruin”.